Coffee international competitiveness and structure of market: analysis from 2003 to 2012 - Thomé, Karim Marini; Ferreira, Lucas Souza (Coffee Science - ISSN 1984-3909, 2015)
The research of international competitiveness of the coffee is of great importance for Brazilian agribusiness since coffee collaborates with a significant portion of the Brazilian trade balance. To better understand the coffee market structure, a quantitative research was performed based on the revealed comparative advantage, relative market position, rate of net exports, market share and concentration index compared to Brazil. Was verified that the coffee market is concentrated, both exports and imports, with little fluctuation between major buyers and sellers throughout the period studied, with exceptions for decrease of Colombian exports and increases in Vietnamese.